Serum oxidizability, total antioxidant status and albumin serum levels in patients with aneurysmal or arterial occlusive disease - Delimaris, I.; Georgopoulos, S.; Kroupis, C.; Zachari, A; Liberi,M.; Bastounis,E.; Dionyssiou-Asteriou, A (Clin.Biochem., 2008)
OBJECTIVES: Oxidative stress is involved in the pathophysiology of atherosclerosis. The aim of the present study was to estimate the extent of oxidative stress in patients with aneurysmal and arterial occlusive disease (AAOD) by analyzing the magnitude of serum oxidizability, total antioxidant status and serum antioxidants and to evaluate their potential clinical significance. DESIGN AND METHODS: The study was conducted on 47 patients with AAOD and 49 healthy individuals. Oxidative stress was assessed by: a) copper-induced lipid oxidation described in terms of "lag-time" (t(LAG)) and "maximal rate of accumulation of absorbing products" (RA) and b) the measurement of serum total antioxidant status (TAS) and hydrophilic serum antioxidants (albumin, uric acid, transferrin, bilirubin). LDL-cholesterol and HDL-cholesterol were also estimated. RESULTS: A decrease of t(LAG) and albumin levels in patients as compared to controls was observed. t(LAG) was negatively correlated with RA in both patients and controls. RA and LDL-cholesterol did not differ between the two groups. HDL-cholesterol was decreased in patients in comparison to controls. There is statistically significant evidence that low albumin serum levels are associated with increased risk of AAOD. CONCLUSIONS: The results support the involvement of oxidative stress in AAOD. Significant alterations in serum oxidizability were found in patients with AAOD and low albumin serum levels were correlated with the disease. Clinical evaluation of both findings needs further investigation
DA - 20080519 IS - 1873-2933 (Electronic) IS - 0009-9120 (Linking) LA - eng PT - Comparative Study PT - Journal Article PT - Research Support, Non-U.S. Gov't RN - 0 (Antioxidants) RN - 0 (Serum Albumin) SB - IM
Keywords: Adult; Aged; Aged,80 and over; analysis; Aneurysm; Antioxidants; Arterial Occlusive Diseases; Blood; Diagnosis; Female; Greece; Humans; Lipid Peroxidation; Male; metabolism; Middle Aged; Oxidative Stress; physiology; Serum albumin